Unfortunately, for now we aren’t the gods of time!.. - Ashursky, Emir E. (Cognition, 2024)
This article is devoted to the overthrow of the idle conjectures of sci-fi writers (and after them some romantically minded astrophysicists), one way or another relating to the notorious time travel. Wherein primary attention here is paid to proof of the absolute conceptual prohibition on moving into the past. After all, according to author’s count, lots of fabrications of the human intelligence are by no means equivalent to the quantity of objects of the so-called Cauchy horizon. And moreover: the ordinal of our generalized spiritual world should be obviously higher than for a similar set of structural elements of the observed cosmos. In particular, if a number of material objects is N, a manifold of their cogitable combinations may vary from 2n to Nn. But still with that, it does not seem possible, however, to refute (as shown yet by Kurt Gödel) the significant majority of these frankly dubious speculations at a physical & mathematical level. Thus precisely the probabilistic approach (or, if you like, algorithm) is a quite legitimate and the only correct for given case! And summarizing, the author leads his reader to a quite reasoned conclusion that unraveling the most complex outlook problems of existence, it is better obviously to trust philosophers rather than naturalists or techies!